Ethical Taxation Through Governance and CSR: Evidence from Indonesian Firms - Nurul Hatari Awalia; Uun Sunarsih (Santoso Academy Network, 2026)
This study examines the influence of independent boards of commissioners, boards of directors, audit committees, and Corporate Social Responsibility (CSR) on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during 2021–2024. The research addresses inconsistent findings regarding the effectiveness of corporate governance and CSR in reducing tax avoidance. Manufacturing firms were selected due to their complex operations, high tax exposure, and significant contribution to Indonesia’s economy. A quantitative associative approach was employed. Using purposive sampling, 53 companies were selected, generating 212 firm-year observations. Secondary data from annual financial and sustainability reports were analyzed using panel regression with EViews. The results show that independent boards of commissioners do not significantly affect tax avoidance, indicating that their monitoring role has not been fully effective in preventing opportunistic tax behavior. In contrast, boards of directors, audit committees, and CSR significantly influence tax avoidance, suggesting that stronger governance mechanisms and greater social responsibility can reduce aggressive tax practices and improve tax compliance. This study contributes to agency and legitimacy theories by emphasizing the importance of effective governance and ethical responsibility in mitigating tax avoidance and promoting sustainable corporate practices.